Explaining the Behavior of Financial Intermediation : Evidence from Transition Economies - Rother, Philipp (IMF Working Papers; Working Paper, 1999)
This paper investigates the effects of macroeconomic and structural variables on financial intermediation. To this end, it presents a theoretical foundation for two new measures of intermediation, the money multiplier and the ratio of private sector credit to monetary base. Results from panel estimations covering 19 transition economies indicate that policy makers need to address in particular the problems of bad loans on bank balance sheets and high market concentration while maintaining a stable macroeconomic environment. Further variables, such as minimum reserve requirements and the capital adequacy ratio, are found to possess less explanatory power.